An Exploration of Frugal Living's Lifestyle Among Migrant Students of Pertamina University: Implications for Identity in Intercultural Communication - Satria Perdana Putra Sunawang; Rijal Padlilah; Dwipa Adi Saputra (Jurnal Indonesia Sosial Sains, 2024)
This research explores the application of frugal living lifestyle among Pertamina University overseas students, focusing on the implications for identity and intercultural communication. The background of this research is the high cost of living in DKI Jakarta, which poses a challenge for overseas students. Frugal living emerged as a solution to overcome this financial challenge, emphasizing smart and disciplined financial management. This research aims to understand how students internalize and communicate frugal living values in their daily lives. This research uses a qualitative approach with an interpretive paradigm. Participants were selected through purposive sampling technique, with the inclusion criteria of overseas students who live a frugal lifestyle.  Primary data were collected through in-depth interviews and observations, while secondary data were obtained from supporting documents and literature. Data analysis was conducted by interpreting the results of interviews and observations to understand the application of frugal living and its implications for identity and intercultural communication patterns. The validity of the research was maintained by selecting the right participants and reaching the information saturation point. The results show that frugal living is not just a financial management strategy, but also reflects the values of simplicity, sustainability, and responsibility. The frugal identity that is formed affects the way students interact with the surrounding environment, strengthens their sense of independence and responsibility, and is recognized as a wise individual in managing finances. The implications of this research can support further understanding of the frugal living lifestyle among overseas students, with a focus on identity formation and intercultural communication.